2021
DOI: 10.1155/2021/1337558
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Syndrome Classification of Non-Small-Cell Lung Cancer Based on Data of Tongue and Pulse with Machine Learning

Abstract: Objective. To explore the data characteristics of tongue and pulse of non-small-cell lung cancer with Qi deficiency syndrome and Yin deficiency syndrome, establish syndrome classification model based on data of tongue and pulse by using machine learning methods, and evaluate the feasibility of syndrome classification based on data of tongue and pulse. Methods. We collected tongue and pulse of non-small-cell lung cancer patients with Qi deficiency syndrome ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“… 37 Many studies have indicated that ANNs are powerful tools for assisting the clinician in the diagnosis and prognosis of various diseases. 38 39 40 Tong et al . 41 stated that ANNs are convenient and reliable models that outperformed LR models in accurately predicting the survival of unresectable pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Many studies have indicated that ANNs are powerful tools for assisting the clinician in the diagnosis and prognosis of various diseases. 38 39 40 Tong et al . 41 stated that ANNs are convenient and reliable models that outperformed LR models in accurately predicting the survival of unresectable pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent stage. In addition to the previous research on the tongue, there were also more studies on the pulse and TCM symptoms (8,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously some studies solely analyzed the Chinese medicine tongue images so that diabetes can be effectively differentiated [[ 55 ]]. Palpation diagnosis is also a non-invasive and effective method for CM practitioners to check the location and extent of a patient's disease, and the data was collected as pulse waveforms data [[ 11 , 56 ]]. These advances mean that CM researchers are facing new challenges with big data as the use of instruments and sensors increases [[ 57 ]].…”
Section: Discussionmentioning
confidence: 99%